2011
DOI: 10.1590/s1413-86702011000300004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different primes for PCR-based diagnosis of cutaneous leishmaniasis

Abstract: Objective: The objective of this study was to analyze different primers that are commonly used in epidemiological studies for the detection of Leishmania DNA by PCR, and to compare them to the conventional direct parasite search for American cutaneous leishmaniasis (ACL) diagnosis. Material and methods: Five pairs of primers, four of them derived from Leishmania kDNA sequences (MP3H-MP1L; B1-B2; LBF1-LBR1; 13A-13B), and one derived from the SL RNA (mini-exon) gene repeat (LU5A-LB3C), reported previously, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…Interestingly, the primer pairs MP3H-MP1L and B1-B2 demonstrated alignments against multiple strains of Leishmania (such as L. braziliensis complex. Although low sensitivity of the primer pair LU5A-LB3C was observed in amplification reactions by Oliveira et al (2011), the findings described herein demonstrated that this primer pair showed high specificity in comparison to other primer pairs, revealing alignments exclusively against sequences of Leishmania (Table 1). In addition, Harris et al (1998) and Gomes et al (2007) also confirm that primers derived from the mini-exon gene, such as oligonucleotides LU5A and LB3C, represent successful tools to detect and characterize DNA in PCR-based diagnosis of distinct species of Leishmania.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Interestingly, the primer pairs MP3H-MP1L and B1-B2 demonstrated alignments against multiple strains of Leishmania (such as L. braziliensis complex. Although low sensitivity of the primer pair LU5A-LB3C was observed in amplification reactions by Oliveira et al (2011), the findings described herein demonstrated that this primer pair showed high specificity in comparison to other primer pairs, revealing alignments exclusively against sequences of Leishmania (Table 1). In addition, Harris et al (1998) and Gomes et al (2007) also confirm that primers derived from the mini-exon gene, such as oligonucleotides LU5A and LB3C, represent successful tools to detect and characterize DNA in PCR-based diagnosis of distinct species of Leishmania.…”
Section: Resultsmentioning
confidence: 58%
“…The findings reported in this study emphasize differentiated degrees of specificity of distinct primer pair sequences employed for molecular Leishmaniasis detection by using comparative search and alignment analyses. The performance of these primer pairs has been tested under experimental approaches, demonstrating their variable sensitivity in PCR-based diagnostics for Leishmania (Oliveira, Lonardoni, Teodoro, Silveira, 2011). According to Oliveira et al (2011), the primers MP3H-MP1L and B1-B2 showed good sensitivity with amplified DNA fragments for strains of the MP3H-MP1L, 13A-13B, B1-B2 and LU5A-LB3C are 70bp, 120bp, 750bp and 146-149bp, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical features and treatment efficacy vary in leishmaniasis according to species. Identification through classical methods is difficult and time consuming, and molecular biology techniques using targets such as the miniexon gene have been used and allow both diagnosis and species identification …”
Section: Introductionmentioning
confidence: 99%
“…Identification through classical methods is difficult and time consuming, and molecular biology techniques using targets such as the miniexon gene have been used and allow both diagnosis and species identification. 11,12,19,20 The aim of this study was to validate PCR with miniexon gene as a diagnostic test for mucocutaneous leishmaniasis using fresh or paraffin-embedded mucosal biopsies comparing it to a composite reference standard used previously by our group and to evaluate performance for species identification.…”
Section: Introductionmentioning
confidence: 99%